Malignant mixed epithelial and stromal tumour of the kidney: a case report and a literature review - Bakavičius, Arnas; Barisienė, Marija; Snicorius, Marius; Valančienė, Dileta; Dasevičius, Darius; Žalimas, Algirdas; Kvaščevičius, Robertas; Ramonas, Henrikas; Sokolovas, Vitalijus; Jankevičius, Feliksas (Acta medica Lituanica, 2018)
Introduction. Mixed epithelial and stromal tumour of the kidney (MEST) is a rare and distinctive neoplasm accounting for 0.2% of all renal cancers. Most of these tumours behave in a benign fashion but 13 cases with malignant transformation have already been reported. We present the first case of an extremely aggressive MEST with rapid recurrence after radical treatment, demonstrating objective response to chemotherapy. Case presentation. A 31-year-old female presented to the hospital complaining of gross hematuria. Computed tomography (CT) revealed an intraparenchymal mass in the left kidney forming a tumour thrombus in the inferior vena cava (IVC). Metastatic disease was ruled out and, under the clinical diagnosis of renal cell carcinoma, left radical nephrectomy with IVC thrombectomy was performed. The histopathological examination confirmed malignant MEST of the kidney. At the follow-up 12 months after surgery, a recurrent tumour in the left paravertebral area and a tumour thrombus in the IVC were detected. A second surgery was recommended and the mass from the paravertebral area was removed, so resection of the IVC with prosthetic replacement was performed. The histopathologic examination confirmed a recurrent malignant MEST. At the follow-up three months after the second surgery disease progression was diagnosed, so chemotherapy with ifosfamide and doxorubicin was initiated. The CT scan performed 14 months after the chemotherapy confirmed a stable process of the disease with no signs of progression. Conclusions. A literature review and our case report confirm the existence of extremely aggressive malignant MEST that shows response to chemotherapy. However, more reports are needed to improve our understanding about the biology of the MEST to develop any recommendations on personalized therapy.
Keywords: Kidney; mixed epithelial and stromal tumour; malignant; surgery; chemotherapy